Penerapan Media Wordwall untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPAS di Kelas IV SD - Ilham Cahyo Firdaus; Vivi Rulviana; Rakini Rakini (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Learning that lacks variety makes students less enthusiastic in learning activities which results in low motivation to learn in students. Therefore, the researcher applied wordwall learning media to increase the learning motivation of grade IV students of SD Taman in the science and science subjects for the 2024/2025 school year. This research aims to increase students' learning motivation through the use of word wall media. The research method used is Classroom Action Research (CAR) which consists of 2 cycles. There are 4 stages in each cycle, namely: Planning, Implementation, Observation, Reflection. The results of the study show that the application of Wordwall media has an impact on the change in attitude that occurs in students after applying learning with Wordwall media. The results of the research obtained were that the learning motivation of students in cycle 1 was 47% in the high category, in cycle II it increased to 93.47% in the very high category. The conclusion of this study is that the use of wordwall media can increase students' learning motivation in learning social studies in grade IV of SD Taman.